1971
DOI: 10.2135/cropsci1971.0011183x001100030021x
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive Segregation and the Nature of Gene Action for Yield in an Intervarietal Cross of Upland Cotton1

Abstract: Two inbred parental lines, their f lt and six inbred lines selected for high yield after three cycles of recurrent selection in this population were evaluated at three locations for two years. The Fj yielded 32.6% more than the midparent value and exceeded the higher parent by 13.3%. The F! also exceeded the midparent values for several components of yield, including lint percentage, weight per boll, number of bolls per plot, lint index, and seed index.The mean yield of the six selected lines exceeded that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
2
2
0
1
Order By: Relevance
“…These results agree with that reported by Thomson and Luckett (1988) and Coyle and Smith (1997). High GCA eVects observed on lint yield and yield components were reported by El-Adl and Miller (1971) and Echekwu and Alaba (1995). These results indicated strong additive genetic variance.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with that reported by Thomson and Luckett (1988) and Coyle and Smith (1997). High GCA eVects observed on lint yield and yield components were reported by El-Adl and Miller (1971) and Echekwu and Alaba (1995). These results indicated strong additive genetic variance.…”
Section: Discussionsupporting
confidence: 93%
“…Highly significant additive and non additive gene effects were indicated by the significance of "a" and "b" items (Table 6) for all traits studied. Similar results were obtained by El-Adl and Miller (1971), El-Fawal et al (1977), El-Kadi et al (1982) and Garg et al (1989). The additive gene effects were greater than dominance gene effects for all studied traits in accordance with the results of El-Kadi et al (1982).…”
Section: Ii-the Diallel Analysissupporting
confidence: 86%
“…For effective and rapid improvement in seedcotton yield, through conventional breeding method, availability of variation among parents 5 in the initial crosses is essential. Estimates of general conbining ability (GCA) from a set of diallel crosses were found to be significant for all traits studied except lint percentage, which demonstrated the importance of additive gene effects of these traits with variance for specific combining ability (SCA) was significant only for lint percentage (El-Adl and Miller, 1971). El-Fawal et al (1978) indicated that the GCA mean squares were significant for seed-cotton and lint yield suggesting that the genetic variation among F1 hybrids was mainly associated with additive genetic effects while SCA estimates were small and significant only for boll weight.…”
Section: Introductionmentioning
confidence: 93%
“…In the same study, the rankings of the lines based on GCA were similar to those based on parental performance, which indicated the predictability of parental performance by their GCA. Lee et al (1967) and El‐Adl and Miller (1971) detected significant GCA for lint yield and fiber properties with no significant GCA × environment in F 1 hybrids. In contrast, Meredith and Bridge (1973) detected significant SCA for lint yield in analysis among 10 F 2 hybrids.…”
mentioning
confidence: 88%